Understanding and Addressing Reading Comprehension Challenges: Magnitude, Causes and Solutions - Getachew Mihret; Jagdish Joshi (Journal of English as A Foreign Language Teaching and Research, 2025)
Reading comprehension is a critical skill that forms the foundation for academic success and lifelong learning. However, many students face difficulties in understanding written texts, which negatively impacts their academic performance and overall literacy development. In Ethiopian secondary schools, poor reading comprehension has become a major concern, yet limited research has investigated the underlying causes and potential solutions within the local context. This study examines the extent and causes of students' reading comprehension difficulties and proposes actionable interventions. Employing a mixed-method research design, the study utilized a stratified random sampling technique to ensure the representation of diverse student subgroups. A total of 105 participants were selected from a population of 145. Data were gathered using a structured questionnaire with closed-ended questions, providing quantitative insights into the severity and nature of the problem. The findings reveal that students' reading comprehension challenges stem from inadequate teaching strategies, a lack of reading materials, and low motivation. The study identifies a significant gap in the existing literature regarding localized solutions to reading comprehension difficulties in Ethiopian secondary schools. Based on the findings, targeted recommendations are proposed, including the adoption of interactive teaching methodologies, enhanced access to reading resources, and teacher training programs aimed at improving pedagogical skills. This research contributes to the body of knowledge on reading comprehension and offers practical strategies for educators, policymakers, and other stakeholders to enhance student's literacy skills and overall academic performance